2011
DOI: 10.1136/bmjopen-2011-000231
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and perceptions of medical students about family medicine in Spain: protocol for a cross-sectional survey: Figure 1

Abstract: BackgroundDespite the fact that family medicine (FM) has become established as a specialty in the past 25 years, this has not been reflected in the inclusion of the specialty in the majority of medical schools in Spain. Almost 40% of the students will work in primary care but, in spite of this, most universities do not have an assessed placement as such. There are only specific practice periods in health centres or some student-selected components with little weight in the overall curricula.ObjectivesTo evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The project methods have been detailed previously [ 12 ]. This article presents the results of the first administration of the survey.…”
Section: Methodsmentioning
confidence: 99%
“…The project methods have been detailed previously [ 12 ]. This article presents the results of the first administration of the survey.…”
Section: Methodsmentioning
confidence: 99%
“…According to studies in other countries, females also have a more positive attitude towards family medicine than males [25]. In contrast to what was commonly believed, another study conducted in egypt and in Morocco concluded there was no statistical difference between males and females regarding their intention to choose family medicine as a future career [26,27].…”
Section: Discussionmentioning
confidence: 87%
“…Although not a multicentre survey (as currently in Spain [22]), it was conducted at very different stages of training: at the beginning and in the penultimate year of study. This allowed analysis of possibly changing attitudes over almost the entire theoretical education.…”
Section: Discussionmentioning
confidence: 99%